On some cluster sets problems - CRISTEA, Mihai (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We generalize some cluster sets theorems of Tsuji and Iversen from plane holomorphic mappings to the class of ring mappings. Mathematics Subject Classification (2010): 30C65 31A15. Received 11 October 2021; Accepted 16 November 2021.